Rutile production method based on redox-acid-base assisted leaching
The titanium slag is processed through the redox-acid-base assisted leaching process, combined with carbon-based reducing agent and acid-base leaching process, and the problem of low-grade titanium slag is solved, and the production of high-quality rutile is achieved, reducing production costs and improving energy-saving effects.
Patent Information
- Application Number
- CN202411539832.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art is difficult to effectively use low-grade titanium slag to produce high-grade rutile, and the traditional arc heating carbon reduction method consumes high power, has high production costs, and is difficult to efficiently remove non-ferrous impurities.
The titanium slag is treated with a redox-acid-base assisted leaching process, and the quality of the titanium oxide slag is improved by ball milling and gradient temperature firing. The reduction treatment is performed using a carbon-based reducing agent, and impurities are removed in combination with alkali leaching and acid leaching processes, and finally rutile is prepared by water leaching and filtration.
It achieves efficient separation and removal of impurities from titanium slag, improves the quality and purity of rutile, reduces production costs, and does not require arc heating, making it more energy-saving.
Smart Images

Figure CN119503870A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium resource utilization, and in particular to a rutile production method based on redox-acid-base leaching. Background Art
[0002] Rutile is a relatively pure titanium dioxide, which is an important mineral raw material for refining titanium, but its reserves in the earth's crust are relatively small. It has excellent properties such as high temperature resistance, low temperature resistance, corrosion resistance, high strength, and low specific gravity, and is widely used in military aviation, aerospace, navigation, machinery, chemical industry, and seawater desalination. Rutile itself is one of the necessary raw materials for high-grade welding rods, and it is also the best raw material for producing rutile titanium dioxide. As a rare metal, although titanium is highly abundant in the earth's crust, its titanium content is usually low due to the dispersed distribution of titanium-containing minerals in titanium slag, and the utilization of titanium resources is difficult. Therefore, it has always been a difficult point in this field to effectively utilize the titanium resources in low-grade titanium slag to produce high-grade rutile, and the development of new separation and purification processes is the key to realizing the utilization of low-grade titanium resources. In order to effectively utilize the titanium resources in low-grade titanium slag, we have conducted a lot of research on the enrichment and separation treatment of electric furnace titanium slag. Now we propose a titanium slag treatment method based on redox-acid-base leaching process to obtain high-grade titanium-rich materials. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a rutile production method based on redox-acid-base leaching.
[0004] The technical solution of the present invention is: a method for producing rutile based on redox-acid-base leaching, comprising the following steps:
[0005] S1. Oxidation-reduction treatment: treating low-grade titanium slag by oxidation process and reduction process in sequence to obtain high-grade titanium slag;
[0006] S2, acid-base treatment: using alkali leaching process and acid leaching process to treat the high titanium slag treated by S1 in sequence to obtain refined titanium slag;
[0007] S3, water immersion treatment: the refined titanium slag obtained in S2 is mixed evenly in pure water to obtain a slurry;
[0008] S4, rutile preparation: filtering, washing and drying the slurry in S3 to obtain rutile;
[0009] In the reduction process of S1, the reducing agent used is a carbon-based reducing agent, and the preparation method of the carbon-based reducing agent is as follows:
[0010] SA1, preparing spinning solution;
[0011] Resorcinol and F127 are placed in DMF, stirred for 30 to 40 minutes, and then ultrasonically treated for 1 hour to 1.5 hours to prepare a spinning solution;
[0012] Let n be the multiplication coefficient and n∈R + , where n can be 1, 2, 3, ...., then the amount of resorcinol added is n[10,20]mmol, the amount of F127 added is n[0.5,1]mmol, and the amount of DMF added is n[10,15]g;
[0013] SA2, preparing fiber silk carrier;
[0014] The spinning solution prepared in SA1 was used as a raw material to prepare a fiber carrier by an electrospinning process;
[0015] The parameters of the electrospinning process are: positive electrode voltage of 20-30 kV, drum speed of 120-130 r / min, receiving distance of 15-17 cm, temperature of 25±2°C, humidity of 25±2%, and injection rate of 0.08-0.1 mm / min;
[0016] SA3, prepare pulling solution;
[0017] Mix 37 wt.% hydrochloric acid, 10 wt.% boric acid and 37 wt.% formaldehyde solution, and stir ultrasonically for 15 to 20 minutes to obtain a pulling solution;
[0018] Let n be the multiplication coefficient and n∈R + , then the amount of 37wt.% hydrochloric acid added is n[5,8]mL, the amount of 10wt.% boric acid added is n[20,25]mL, and the amount of 37wt.% formaldehyde solution added is n[30,40]mL;
[0019] SA4, fiber processing;
[0020] The fiber carrier prepared in SA2 is fixed on an impregnation and pulling machine, immersed in the pulling liquid prepared in SA3, and the fiber is obtained by pulling. The pulling speed is set to 2-3 mm / s, and the immersion time is 4-6 h.
[0021] SA5. Preparation of carbon-based reducing agent;
[0022] First, the fiber filaments in SA4 are dried at 100°C for 24 hours, then washed with pure water and dried at 60°C for 20-30 minutes, and finally heated at a gradient temperature. After the reaction is complete, the fiber filaments are cooled to room temperature in the furnace to obtain a carbon-based reducing agent.
[0023] The gradient temperature in the SA5 is: rising from room temperature to 100°C at a rate of 1-2°C / min, and keeping warm for 10-15min; then rising to 600°C at a rate of 3-5°C / min, and keeping warm for 2-3h.
[0024] Description: By preparing and using boron-doped porous carbon filaments, on the one hand, boron can generate boron oxide by releasing oxygen in the subsequent reduction reaction, thereby reducing the formation of perovskite in low-grade titanium slag in the subsequent crystallization process and increasing the formation ratio of pyrophyllite; on the other hand, C can be used as a reducing agent to greatly capture the oxygen in the low-grade titanium slag, and TiO2b is reduced to Ti3O5, which will dissolve other impurities and is conducive to the formation of pyrophyllite, thereby gradually increasing the leaching rate of impurities such as Fe2O3, MgO, Al2O3, and MnO.
[0025] Further, the oxidation process in S1 is:
[0026] S1-1, firstly, the low-grade titanium slag is ground to 100-150 μm by ball milling process, and then dried at 100°C for 3-4 hours;
[0027] The parameters of ball milling process are: the speed of material tank is 60-70rpm, the speed of chassis is 200-220rpm, the ball milling time is 20-25min, and the ball-to-material ratio is 4:1;
[0028] S1-2, sintering the low-grade titanium slag treated in S1-1 at a gradient temperature, and finally cooling it to room temperature with the furnace to obtain titanium oxide slag, i.e., high-titanium slag;
[0029] The gradient temperature in S1-2 is: rising from room temperature to 100°C at a rate of 10-15°C / min, and keeping warm for 5-10 minutes; then rising to 500°C at a rate of 10-15°C / min, and keeping warm for 30-40 minutes; finally rising to 1100°C at a rate of 15-20°C / min, and keeping warm for 1-1.5 hours.
[0030] Description: Low-grade titanium slag is continuously crushed by ball milling to significantly reduce its particle size, and then ground into fine powder for subsequent gradient temperature firing. Gradient temperature firing can help achieve uniform temperature distribution inside the low-grade titanium slag, reduce internal stress or defects caused by uneven temperature, and improve oxidation effect, thereby obtaining excellent titanium oxide slag.
[0031] Furthermore, the reduction process in S1 is:
[0032] S1-3, uniformly mixing the titanium oxide slag in S1-2 with the carbon-based reducing agent, and cold isostatically pressing at 60-100 MPa in a mold to form a titanium slag blank;
[0033] Let n be the multiplication coefficient and n∈R+ , then the amount of titanium oxide slag added in S1-3 is n[20,25]g, and the amount of carbon-based reducing agent added is n[2,3]g;
[0034] S1-4, placing the titanium slag blank in a tubular furnace for heating, firstly introducing an inert gas (such as nitrogen) at a rate of 2 to 2.5 L / min, and exhausting for 10 to 15 minutes; then performing a reduction reaction at a gradient temperature, and cooling the furnace to room temperature to obtain reduced titanium slag;
[0035] The gradient temperature in S1-4 is: rising from room temperature to 100°C at a rate of 10-15°C / min, and keeping warm for 5-10 minutes; then rising to 700°C at a rate of 10-15°C / min, and keeping warm for 20-30 minutes; then rising to 850°C at a rate of 15-20°C / min, and keeping warm for 20-30 minutes; then rising to 900°C at a rate of 20-25°C / min, and keeping warm for 1-1.5 hours.
[0036] Note: Different reduction temperatures will affect the phase composition of titanium slag. When the reduction temperature is lower than 800°C, the main phases of titanium slag are rutile (TiO2), FeTi2O5-MgTi2O5 solid solution, free SiO2, and silicate; at 800°C-900°C, the main phases of titanium slag are rutile (TiO2), ilmenite (FeTiO3), FeTi2O5-MgTi2O5 solid solution, free SiO2, and silicate; when the reduction temperature is higher than 900°C, the main phases of titanium slag are rutile (TiO2), ilmenite, free SiO2, and silicate; therefore, by controlling the temperature of the reduction process at 800°C-900°C, the main phases of titanium slag can be rutile (TiO2), ilmenite (FeTiO3), FeTi2O5-MgTi2O5 solid solution, free SiO2, and silicate, thereby meeting our processing requirements for the reduction process.
[0037] Furthermore, the alkali leaching process in S2 is:
[0038] S2-1, placing the high titanium slag treated by S1 into a high pressure reactor, adding 30wt.% NaOH solution and mixing evenly, and then performing alkali leaching to obtain alkali leached titanium slag;
[0039] The liquid-solid ratio of 20wt.% NaOH solution to high-titanium slag is 3-4:1, the oxygen partial pressure is 1-1.5MPa, the alkali leaching temperature is 180-210°C, and the leaching time is 1.5-2h.
[0040] Description: Sodium hydroxide solution can react with silicon in titanium slag to generate soluble sodium silicate, thereby effectively removing silicon impurities in titanium slag, which is crucial to improving the taste of titanium slag and the performance of subsequent processed products. In addition to silicon, sodium hydroxide can also react with impurity elements such as aluminum, calcium, and magnesium in titanium slag to generate corresponding soluble salts to further purify the titanium slag. By using the above-mentioned alkali-slag ratio, reaction temperature, sodium hydroxide concentration and other alkali leaching conditions, the alkali leaching treatment effect can be significantly improved, thereby improving the purity of subsequent rutile production.
[0041] Furthermore, the acid leaching process in S2 is:
[0042] S2-2, placing the alkali-leached titanium slag in S2-1 into a high-pressure reactor, adding 30wt.% H2SO4 solution and mixing evenly, and then performing acid leaching to obtain acid-leached titanium slag, i.e., refined titanium slag;
[0043] Among them, the liquid-to-solid ratio of 20wt.% H2SO4 solution to alkaline leached titanium slag is 8-10:1, the oxygen partial pressure is 2.5-3MPa, the acid leaching temperature is 80-120°C, and the leaching time is 2-3h.
[0044] Note: By using the above acid-slag ratio, reaction temperature, sulfuric acid concentration and other acid leaching conditions, the acid leaching treatment effect can be significantly improved, thereby improving the purity of the subsequent rutile production.
[0045] Furthermore, the water immersion process in S3 is:
[0046] The refined titanium slag treated with S2 is placed in a reactor, pure water is added and mixed evenly, and water-immersed to obtain slurry;
[0047] Among them, the liquid-solid ratio of pure water to refined titanium slag is 5-10:1, the water immersion temperature is 45-60°C, and the water immersion time is 20-30 minutes.
[0048] Note: The appropriate ratio of pure water to refined titanium slag and the water immersion temperature can improve the leaching efficiency of refined titanium slag. At the same time, by accurately controlling the water immersion temperature, the purity and recovery rate of the product can be improved, further reducing costs.
[0049] Furthermore, the rutile preparation process in S4 is as follows: filtering the slurry in S3, washing the filtered residue with pure water until it is neutral, and then drying at 60° C. for 1 to 2 hours to obtain powdered rutile.
[0050] Note: Acidic substances can be removed by washing the filter residue with pure water. If these substances remain in the filter residue, they may not only affect the subsequent utilization value of the filter residue, but also pollute the environment. At the same time, the acidic substances contained in the filter residue may react with other ingredients during the drying process, resulting in a decrease in product quality. By washing to neutrality, this risk can be eliminated, ensuring the stability and safety of the product and improving the purity of the product.
[0051] The beneficial effects of the present invention are:
[0052] The present invention reports a method for producing rutile based on redox-acid-base leaching. Through the prepared boron-doped porous carbon filaments, boron can react to release oxygen to generate boron oxide in a subsequent reduction reaction, and reduce the generation of perovskite in low-grade titanium slag in a subsequent crystallization process, thereby increasing the generation ratio of black titanium stone. At the same time, carbon can be used as a reducing agent to capture oxygen in the low-grade titanium slag to a great extent, and impurities such as Fe2O3, MgO, CaO, Al2O3, and MnO can be efficiently separated, thereby producing high-quality rutile.
[0053] Compared with the traditional arc heating carbon reduction method, the method of the present invention also has the following advantages:
[0054] 1) Since the arc heating of the conventional arc heating carbon reduction method consumes a large amount of electric energy, which increases the production cost, the method of the present invention does not require arc heating, so it is more energy-efficient and has lower production costs;
[0055] 2) At the same time, although the traditional arc heating carbon reduction method can effectively reduce the iron oxide in the titanium slag to metallic iron, and remove some impurities by melting and separating the slag iron, the removal effect of other non-iron impurities is not ideal. The present invention can efficiently separate impurities such as Fe2O3, MgO, CaO, Al2O3, MnO, etc., thereby producing high-quality rutile;
[0056] 3) The traditional arc heating carbon reduction method involves multiple steps and links, including batching, pelletizing, arc smelting, slag and iron separation, etc., and the performance of the obtained product is not very ideal. The present invention can significantly enhance the quality of the produced rutile by optimizing the oxidation-reduction treatment method and other methods, and obtain high-quality rutile. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 The present invention is a method flow chart of the rutile production method based on redox-acid-base leaching. DETAILED DESCRIPTION
[0058] The present invention is further described in detail below in conjunction with specific implementation methods to better reflect the advantages of the present invention.
[0059] Example 1: A method for producing rutile based on redox-acid-base leaching, such as Figure 1 As shown, the following steps are included:
[0060] S1. Oxidation-reduction treatment: treating low-grade titanium slag by oxidation process and reduction process in sequence to obtain high-grade titanium slag;
[0061] Among them, the oxidation process is:
[0062] S1-1. First, the low-grade titanium slag was ground to 100-150 μm using a ball milling process, and then dried at 100°C for 3.5 hours. The parameters of the ball milling process were: the material tank speed was 65 rpm, the chassis speed was 210 rpm, the ball milling time was 23 minutes, and the ball-to-material ratio was 4:1.
[0063] S1-2, the low-grade titanium slag treated by S1-1 is fired at a gradient temperature, and finally cooled to room temperature with the furnace to obtain titanium oxide slag, i.e., high-titanium slag; the gradient temperature in S1-2 is: from room temperature to 100°C at a rate of 12°C / min, and kept warm for 8 minutes; then raised to 500°C at a rate of 12°C / min, and kept warm for 37 minutes; finally raised to 1100°C at a rate of 18°C / min, and kept warm for 1.3 hours;
[0064] The reduction process is:
[0065] S1-3, the titanium oxide slag in S1-2 is mixed evenly with the carbon-based reducing agent, and cold isostatically pressed in a mold at 80 MPa to form a titanium slag blank; n is the multiplication factor and n∈R + , n is 1, then the amount of titanium oxide slag added in S1-3 is 23g, and the amount of carbon-based reducing agent added is 2.7g;
[0066] S1-4, the titanium slag blank is placed in a tubular furnace for heating, firstly nitrogen is introduced at a rate of 2.3L / min, and the exhaust is carried out for 12min; then reduction reaction is carried out at a gradient temperature, and the reduced titanium slag is obtained after the furnace is cooled to room temperature; the gradient temperature in S1-4 is: from room temperature to 100°C at a rate of 13°C / min, and the temperature is kept for 7min; then the temperature is increased to 700°C at a rate of 12°C / min, and the temperature is kept for 25min; then the temperature is increased to 850°C at a rate of 18°C / min, and the temperature is kept for 25min; then the temperature is increased to 900°C at a rate of 23°C / min, and the temperature is kept for 1.3h;
[0067] The preparation method of the above-mentioned carbon-based reducing agent is as follows:
[0068] SA1, preparing spinning solution;
[0069] Resorcinol and F127 were placed in DMF, stirred for 35 min and then ultrasonically treated for 1.3 h to prepare a spinning solution; n is the rate coefficient and n∈R+ , n is 1, then the amount of resorcinol added is 15mmol, the amount of F127 added is 0.8mmol, and the amount of DMF added is 13g;
[0070] SA2, preparing fiber silk carrier;
[0071] The spinning solution prepared in SA1 was used as a raw material to prepare a fiber carrier by an electrospinning process; the parameters of the electrospinning process were: positive electrode voltage of 27 kV, drum speed of 125 r / min, receiving distance of 16 cm, temperature of 25° C., humidity of 25%, and injection rate of 0.09 mm / min;
[0072] SA3, prepare pulling solution;
[0073] 37wt.% hydrochloric acid, 10wt.% boric acid and 37wt.% formaldehyde solution were mixed and ultrasonically stirred for 18min to obtain a pulling solution; n is the rate coefficient and n∈R + , n is 1, then the amount of 37wt.% hydrochloric acid added is 7mL, the amount of 10wt.% boric acid added is 23mL, and the amount of 37wt.% formaldehyde solution added is 38mL;
[0074] SA4, fiber processing;
[0075] The fiber carrier prepared in SA2 was fixed on an impregnation and pulling machine, immersed in the pulling liquid prepared in SA3, and the fiber was obtained by pulling. The pulling speed was set to 2.5 mm / s and the immersion time was 5 h.
[0076] SA5. Preparation of carbon-based reducing agent;
[0077] First, the fiber filaments in SA4 are dried at 100°C for 24 hours, then washed with pure water and dried at 60°C for 25 minutes, and finally heated at a gradient temperature. After the reaction is complete, the fiber filaments are cooled to room temperature in the furnace to obtain a carbon-based reducing agent; the gradient temperature in the SA5 is: increased from room temperature to 100°C at a rate of 1.5°C / min, and kept warm for 13 minutes; then increased to 600°C at a rate of 4°C / min, and kept warm for 2.5 hours.
[0078] S2, acid-base treatment: using alkali leaching process and acid leaching process to treat the high titanium slag treated by S1 in sequence to obtain refined titanium slag;
[0079] Among them, the alkali leaching process is:
[0080] S2-1, placing the high titanium slag treated by S1 into a high-pressure reactor, adding 30wt.% NaOH solution and mixing evenly, and then performing alkali leaching to obtain alkali-leached titanium slag; wherein the liquid-solid ratio of 30wt.% NaOH solution to high titanium slag is 3.7:1, the oxygen partial pressure is 1.3MPa, the alkali leaching temperature is 205°C, and the leaching time is 1.8h;
[0081] The acid leaching process is:
[0082] S2-2, placing the alkali-leached titanium slag in S2-1 into a high-pressure reactor, adding 30wt.% H2SO4 solution and mixing evenly, and then performing acid leaching to obtain acid-leached titanium slag, i.e., refined titanium slag; wherein, the liquid-solid ratio of the 30wt.% H2SO4 solution to the alkali-leached titanium slag is 9:1, the oxygen partial pressure is 2.8MPa, the acid leaching temperature is 110°C, and the leaching time is 2.5h;
[0083] S3, water immersion treatment: put the refined titanium slag obtained in S2 into a reactor, add pure water and mix evenly, perform water immersion treatment, and obtain slurry; wherein, the liquid-solid ratio of pure water to refined titanium slag is 9:1, the water immersion temperature is 55°C, and the water immersion time is 25 minutes;
[0084] S4. Preparation of rutile: Filter the slurry in S3, wash the filtered residue with pure water until it becomes neutral, and then dry it at 60° C. for 1.5 h to obtain powdered rutile.
[0085] In order to explore the quality of rutile prepared by the above method, the TiO2 content of the high-quality rutile is measured, and a control is set up at the same time. The control is as follows:
[0086] Control 1: Add sufficient 98wt% concentrated sulfuric acid to the blast furnace titanium slag to completely immerse the blast furnace titanium, react at 170°C for 1h, then add ultrapure water to reduce the mass concentration of concentrated sulfuric acid to 60wt%, and soak in water at a temperature of 60°C for 2h to obtain slurry A; then filter the slurry A and wash it 5 times with distilled water at a temperature of 80°C to obtain filtrate A and filter residue A, and dry the filter residue A; place the filter residue A in a sealed agitator, add 15% hydrochloric acid to completely immerse the filter residue A, react at 70°C for 1h to obtain slurry B, and then filter the slurry B to obtain filtrate B and filter residue B; place the filter residue B in a sealed reactor, add 10% sodium hydroxide to completely immerse the filter residue B, remove impurities at 115°C for 2h, filter after the reaction and wash it 3 times with distilled water, and dry it at 105°C to obtain rutile.
[0087] Control 2: Based on Example 1, only the carbon-based reducing agent is not added in the reduction process, and other process parameters remain unchanged.
[0088] Then, the TiO2 content of the rutile prepared in Example 1 and the rutile prepared in the control was measured, and the measuring method was as follows:
[0089] 1) Preparation of titanium standard solution: weigh 0.1000g of titanium dioxide (spectrally pure) dried at 105°C into a 30mL porcelain crucible, add 6g of potassium pyrosulfate, cover the crucible, place the crucible in a muffle furnace, gradually raise the temperature from room temperature 25°C to 850°C to melt into a dark red fluid; take out and cool, place the porcelain crucible in a 250mL beaker, heat and dissolve it with sulfuric acid (5+95) solution, take it out and cool, transfer it to a 100mL volumetric flask, dilute it to the scale with sulfuric acid (5+95) solution, shake well, and the titanium standard solution contains 1000ug / mL of titanium dioxide;
[0090] 2) Analysis process: weigh 0.1000g of rutile prepared in Example 1 and control into a high-aluminum crucible, add 3g of sodium hydroxide and mix well, then cover with a layer of sodium peroxide (1g), put the high-aluminum crucible into a 700°C muffle furnace for 12min to melt to a dark red fluid, take out and cool, place the high-aluminum crucible in a 250mL beaker, add 20mL of water to soak the frit, and cover with a watch glass. After the frit is dissolved, wash out the high-aluminum crucible with water, heat and boil for 10min, remove and cool, filter and wash the precipitate with distilled water 3 times, dissolve the precipitate in a 100mL volumetric flask with sulfuric acid (1+1), dilute to the scale with distilled water, mix well, and clarify;
[0091] Pipette 10.00mL into a 50mL volumetric flask, add 2mL phosphoric acid (1+1) solution and 5mL sulfuric acid (1+1) solution, dilute to 40mL with distilled water, shake well, add 5mL hydrogen peroxide (10+90) solution, dilute to scale with distilled water, shake well, after 10 minutes, measure the absorbance of titanium at a wavelength of 400-420nm with a 2cm cuvette, and perform a blank test together with the sample solution to be tested;
[0092] In a group of 50mL volumetric flasks, 0, 100, 200, 400, 600, 800, 1000, 2000, 3000, 4000, 5000ug titanium dioxide standard solution were added respectively, and a standard curve was drawn. The corresponding TiO2 content was obtained on the standard curve according to the absorbance of the sample solution to be tested. The TiO2 content in the high-quality rutile prepared in Example 1 and the rutile prepared by the control is shown in Table 1:
[0093] Table 1 Statistics of TiO2 content in rutile
[0094]
[0095]
[0096] It can be seen from Table 1 that the high-quality rutile prepared by the method in Example 1 can make the TiO2 content greater than 99%, and the main difference between Control 1 and Example 1 is that a different titanium slag treatment process is used, and the main difference between Control 2 and Example 1 is that no carbon-based reducing agent is used. The TiO2 content in the rutile prepared by the methods of Control 1 and Control 2 is significantly lower than that of the high-quality rutile prepared in Example 1. It can be seen that by using boron-doped porous carbon filaments, the leaching rate of impurities such as Fe2O3, MgO, Al2O3, and MnO in low-grade titanium slag can be increased, thereby effectively improving the quality of rutile.
[0097] Example 2: This example differs from Example 1 in that the ball milling parameters of the oxidation process in step S1 are, specifically, firstly, the low-grade titanium slag is ground to 100-150 μm using a ball milling process, and then dried at 100°C for 3 hours; the parameters of the ball milling process are: the material tank speed is 60 rpm, the chassis speed is 200 rpm, the ball milling time is 20 min, and the ball-to-material ratio is 4:1.
[0098] Example 3: This example differs from Example 1 in that the ball milling parameters of the oxidation process in step S1 are, specifically, firstly, the low-grade titanium slag is ground to 100-150 μm using a ball milling process, and then dried at 100°C for 4 hours; the parameters of the ball milling process are: the material tank speed is 70 rpm, the chassis speed is 220 rpm, the ball milling time is 25 min, and the ball-to-material ratio is 4:1.
[0099] Example 4: This example differs from Example 1 in that the firing parameters of the oxidation process in step S1, specifically, the gradient temperature in S1-2 is: from room temperature to 100°C at a rate of 10°C / min, and kept warm for 5 minutes; then increased to 500°C at a rate of 10°C / min, and kept warm for 30 minutes; finally increased to 1100°C at a rate of 15°C / min, and kept warm for 1 hour.
[0100] Example 5: This example differs from Example 1 in that the firing parameters of the oxidation process in step S1, specifically, the gradient temperature in S1-2 is: from room temperature to 100°C at a rate of 15°C / min, and keep warm for 10 min; then increase to 500°C at a rate of 15°C / min, and keep warm for 40 min; finally increase to 1100°C at a rate of 20°C / min, and keep warm for 1.5 h.
[0101] Example 6: This example is different from Example 1 in that the mixing parameters of the reduction process in step S1, specifically, S1-3, uniformly mixing the titanium oxide slag in S1-2 with the carbon-based reducing agent, and cold isostatically pressing at 60 MPa in a mold to form a titanium slag blank; n is the rate coefficient and n∈R +, n is 1, then the amount of titanium oxide slag added to S1-3 is 20g, and the amount of carbon-based reducing agent added is 2g.
[0102] Example 7: This example is different from Example 1 in that the mixing parameters of the reduction process in step S1, specifically, S1-3, uniformly mixing the titanium oxide slag in S1-2 with the carbon-based reducing agent, and cold isostatically pressing at 100 MPa in a mold to form a titanium slag blank; n is the rate coefficient and n∈R + , n is 1, then the amount of titanium oxide slag added to S1-3 is 25g, and the amount of carbon-based reducing agent added is 3g.
[0103] Example 8: The difference between this example and Example 1 lies in the heating parameters of the reduction process in step S1, specifically, S1-4, placing the titanium slag blank in a tubular furnace for heating, first introducing nitrogen at a rate of 2L / min and exhausting for 10 minutes; then carrying out a reduction reaction at a gradient temperature, and obtaining reduced titanium slag after cooling to room temperature with the furnace; the gradient temperature in S1-4 is: from room temperature to 100°C at a rate of 10°C / min, and keeping warm for 5 minutes; then increasing to 700°C at a rate of 10°C / min, and keeping warm for 20 minutes; secondly increasing to 850°C at a rate of 15°C / min, and keeping warm for 20 minutes; then increasing to 900°C at a rate of 20°C / min, and keeping warm for 1 hour.
[0104] Example 9: The difference between this example and Example 1 lies in the heating parameters of the reduction process in step S1, specifically, S1-4, placing the titanium slag blank in a tubular furnace for heating, first introducing nitrogen at a rate of 2.5L / min and exhausting for 15 minutes; then carrying out a reduction reaction at a gradient temperature, and obtaining reduced titanium slag after cooling to room temperature with the furnace; the gradient temperature in S1-4 is: from room temperature to 100°C at a rate of 15°C / min, and keeping warm for 10 minutes; then increasing to 700°C at a rate of 15°C / min, and keeping warm for 30 minutes; secondly increasing to 850°C at a rate of 20°C / min, and keeping warm for 30 minutes; then increasing to 900°C at a rate of 25°C / min, and keeping warm for 1.5 hours.
[0105] Example 10: This example is different from Example 1 in that the spinning solution preparation parameters of the carbon-based reducing agent in step S1 are as follows: resorcinol and F127 are placed in DMF, stirred for 30 minutes and then ultrasonically treated for 1 hour to prepare the spinning solution; n is the rate coefficient and n∈R + , n is 1, then the amount of resorcinol added is 10 mmol, the amount of F127 added is 0.5 mmol, and the amount of DMF added is 10 g.
[0106] Example 11: This example is different from Example 1 in that the spinning solution preparation parameters of the carbon-based reducing agent in step S1 are as follows: resorcinol and F127 are placed in DMF, stirred for 40 min, and then ultrasonically treated for 1.5 h to prepare the spinning solution; n is the rate coefficient and n∈R + , n is 1, then the amount of resorcinol added is 20 mmol, the amount of F127 added is 1 mmol, and the amount of DMF added is 15 g.
[0107] Example 12: The difference between this example and Example 1 lies in the preparation parameters of the fiber filament carrier of the carbon-based reducing agent in step S1. Specifically, the fiber filament carrier is prepared by an electrospinning process using the spinning solution prepared in SA1 as raw material; the parameters of the electrospinning process are: positive electrode voltage is 20 kV, drum speed is 120 r / min, receiving distance is 15 cm, temperature is 23°C, humidity is 23%, and injection rate is 0.08 mm / min.
[0108] Example 13: The difference between this example and Example 1 lies in the preparation parameters of the fiber filament carrier of the carbon-based reducing agent in step S1. Specifically, the fiber filament carrier is prepared by an electrospinning process using the spinning solution prepared in SA1 as raw material; the parameters of the electrospinning process are: positive electrode voltage is 30 kV, drum speed is 130 r / min, receiving distance is 17 cm, temperature is 27°C, humidity is 27%, and injection rate is 0.1 mm / min.
[0109] Example 14: This example is different from Example 1 in that the preparation parameters of the carbon-based reducing agent pulling solution in step S1 are, specifically, 37wt.% hydrochloric acid, 10wt.% boric acid and 37wt.% formaldehyde solution are mixed and ultrasonically stirred for 15min to obtain the pulling solution; n is the rate coefficient and n∈R + , n is 1, then the amount of 37wt.% hydrochloric acid added is 5mL, the amount of 10wt.% boric acid added is 20mL, and the amount of 37wt.% formaldehyde solution added is 30mL.
[0110] Example 15: This example is different from Example 1 in that the preparation parameters of the carbon-based reducing agent pulling solution in step S1 are, specifically, 37wt.% hydrochloric acid, 10wt.% boric acid and 37wt.% formaldehyde solution are mixed and ultrasonically stirred for 20min to obtain the pulling solution; n is the rate coefficient and n∈R + , n is 1, then the amount of 37wt.% hydrochloric acid added is 8mL, the amount of 10wt.% boric acid added is 25mL, and the amount of 37wt.% formaldehyde solution added is 40mL.
[0111] Example 16: The difference between this example and Example 1 lies in the preparation parameters of the carbon-based reducing agent in step S1. Specifically, the fiber filaments in SA4 are first dried at 100°C for 24 hours, then washed with pure water and dried at 60°C for 20 minutes, and finally heated at a gradient temperature. After the reaction is complete, the fiber filaments are cooled to room temperature with the furnace to obtain a carbon-based reducing agent. The gradient temperature in SA5 is: from room temperature to 100°C at a rate of 1°C / min, and kept warm for 10 minutes; then increased to 600°C at a rate of 3°C / min, and kept warm for 2 hours.
[0112] Example 17: The difference between this example and Example 1 lies in the preparation parameters of the carbon-based reducing agent in step S1. Specifically, the fiber filaments in SA4 are first dried at 100°C for 24 hours, then washed with pure water and dried at 60°C for 30 minutes, and finally heated at a gradient temperature. After the reaction is complete, the fiber filaments are cooled to room temperature with the furnace to obtain a carbon-based reducing agent. The gradient temperature in SA5 is: from room temperature to 100°C at a rate of 2°C / min, and kept warm for 15 minutes; then increased to 600°C at a rate of 5°C / min, and kept warm for 3 hours.
[0113] In order to explore the influence of various process parameters of S1 in the method of the present invention on the quality of the prepared rutile, the above-mentioned determination method is used to respectively determine the TiO2 content in the rutile prepared in the above-mentioned embodiments, and the results are shown in Table 2:
[0114] Table 2 Statistics of TiO2 content in rutile
[0115]
[0116]
[0117] It can be seen from Table 2 that the high-quality rutile prepared in each embodiment can make the TiO2 content greater than 99%, and the quality of the prepared rutile is affected to a certain extent under different S1 process parameters, and the following exploration is made:
[0118] 1. Investigate the effect of ball milling treatment in different oxidation processes in S1 on the quality of subsequent rutile preparation:
[0119] By comparing Example 2 and Example 3 with Example 1, the quality of the prepared rutile decreased due to lowering the parameters of the ball milling process on the basis of Example 1. This may be due to the failure to fully ball mill the low-grade titanium slag, thereby affecting the quality of the titanium oxide slag obtained by the subsequent oxidation treatment. At the same time, the quality of the prepared rutile did not change significantly by improving the ball milling process on the basis of Example 1 (taking into account factors such as measurement errors, the difference was within ±0.03 and there was no significant change). This may be due to the fact that the low-grade titanium slag was fully ball milled under the parameters of Example 1, and the power consumption of the ball milling process in Example 1 was lower than that in Example 3. Therefore, from the perspective of economy, the ball milling process parameters of Example 1 are relatively optimal.
[0120] 2. Investigate the effect of firing parameters in different oxidation processes in S1 on the quality of subsequent rutile preparation:
[0121] By comparing Example 4 and Example 5 with Example 1, lowering the firing parameters on the basis of Example 1 resulted in a decrease in the quality of the prepared rutile, while increasing the firing parameters on the basis of Example 1 resulted in a decrease in the quality of the prepared rutile. Therefore, the production effect of Example 1 is relatively better.
[0122] 3. Investigate the influence of mixing parameters in different reduction processes in S1 on the quality of subsequent rutile preparation:
[0123] By comparing Example 6 and Example 7 with Example 1, reducing the amount of titanium oxide slag and carbon-based reducing agent added on the basis of Example 1 resulted in a certain degree of decline in the quality of the subsequently prepared rutile, while increasing the amount of titanium oxide slag and carbon-based reducing agent added on the basis of Example 1 resulted in no significant change in the quality of the subsequently prepared rutile. In Example 7, the cold isostatic pressing parameters are higher and the amount of carbon-based reducing agent used is more during production. From the perspective of production economy, the comprehensive production effect of Example 1 is relatively better.
[0124] 4. Investigate the effect of heating parameters in different reduction processes in S1 on the quality of subsequent rutile preparation:
[0125] By comparing Example 8 and Example 9 with Example 1, lowering the heating parameters on the basis of Example 1 resulted in a decrease in the quality of the prepared rutile, and increasing the heating parameters on the basis of Example 1 resulted in a decrease in the quality of the prepared rutile; therefore, the production effect of Example 1 is relatively better.
[0126] 5. Investigate the effect of different spinning solution preparation parameters in S1 carbon-based reducing agent on the quality of subsequent rutile preparation:
[0127] By comparing Example 10 and Example 11 with Example 1, reducing the ultrasonic treatment parameters of the spinning solution and the amount of raw materials on the basis of Example 1 resulted in a decrease in the quality of the prepared rutile, while increasing the ultrasonic treatment parameters of the spinning solution and the amount of raw materials on the basis of Example 1 resulted in no significant change in the quality of the prepared rutile. However, Example 11 used a longer treatment time and raw material dosage, and its economic efficiency was poor, so the comprehensive production effect of Example 1 was relatively better.
[0128] 6. Investigate the effect of different fiber carrier preparation parameters in S1 carbon-based reducing agent on the quality of subsequent rutile preparation:
[0129] By comparing Example 12 and Example 13 with Example 1, lowering the preparation parameters of the fiber filament carrier on the basis of Example 1 resulted in a decrease in the quality of the prepared rutile, while increasing the preparation parameters of the fiber filament carrier on the basis of Example 1 resulted in a decrease in the quality of the prepared rutile. Therefore, the production effect of Example 1 is relatively better.
[0130] 7. Investigate the effect of different pulling solution preparation parameters in S1 carbon-based reducing agent on the quality of subsequent rutile preparation:
[0131] By comparing Example 14 and Example 15 with Example 1, reducing the ultrasonic stirring parameters of the pulling liquid and the amount of raw materials on the basis of Example 1 resulted in a decrease in the quality of the prepared rutile, while increasing the ultrasonic stirring parameters of the pulling liquid and the amount of raw materials on the basis of Example 1 resulted in no significant change in the quality of the prepared rutile. However, Example 15 used a longer processing time and raw material dosage, and its economic efficiency was poor, so the comprehensive production effect of Example 1 was relatively better.
[0132] 8. Investigate the effect of different preparation parameters of carbon-based reducing agent in S1 on the quality of subsequent rutile preparation:
[0133] By comparing Example 16 and Example 17 with Example 1, lowering the preparation parameters of the carbon-based reducing agent on the basis of Example 1 resulted in a decrease in the quality of the prepared rutile, while increasing the preparation parameters of the carbon-based reducing agent on the basis of Example 1 resulted in a decrease in the quality of the prepared rutile. Therefore, the production effect of Example 1 is relatively better.
[0134] Example 18: This example differs from Example 1 in that the alkali leaching process parameters in step S2 are, specifically, a liquid-solid ratio of 30 wt.% NaOH solution to high titanium slag of 3:1, an oxygen partial pressure of 1 MPa, an alkali leaching temperature of 180°C, and a leaching time of 1.5 h.
[0135] Example 19: This example differs from Example 1 in that the alkali leaching process parameters in step S2 are, specifically, a liquid-solid ratio of 30 wt.% NaOH solution to high titanium slag of 4:1, an oxygen partial pressure of 1.5 MPa, an alkali leaching temperature of 210°C, and a leaching time of 2 h.
[0136] Example 20: This example differs from Example 1 in that the acid leaching process parameters in step S2, specifically, the liquid-solid ratio of 30wt.% H2SO4 solution to alkaline leached titanium slag is 8:1, the oxygen partial pressure is 2.5MPa, the acid leaching temperature is 80°C, and the leaching time is 2h.
[0137] Example 21: This example differs from Example 1 in that the acid leaching process parameters in step S2 are, specifically, a liquid-solid ratio of 30 wt.% H2SO4 solution to alkaline leached titanium slag of 10:1, an oxygen partial pressure of 3 MPa, an acid leaching temperature of 120°C, and a leaching time of 3 h.
[0138] In order to explore the influence of various production parameters of S2 on the quality of the prepared rutile in the method of the present invention, the above-mentioned determination method is used to respectively determine the TiO2 content in the rutile prepared in the above-mentioned embodiments, and the results are shown in Table 3:
[0139] Table 3 Statistics of TiO2 content in rutile
[0140] Group <![CDATA[TiO2 content / %]]> Embodiment 18 99.24 Embodiment 19 99.48 Embodiment 20 99.31 Embodiment 21 99.50
[0141] It can be seen from Table 3 that the high-quality rutile prepared in each embodiment can make the TiO2 content greater than 99%, and the quality of the prepared rutile is affected to a certain extent under different S2 production parameters, and the following exploration is made:
[0142] 1. Explore the effects of different alkali leaching processes in S2 on the quality of subsequent rutile preparation:
[0143] By comparing Example 18 and Example 19 with Example 1, lowering the relevant parameters of the alkali leaching process on the basis of Example 1 resulted in a decrease in the quality of the prepared rutile, while increasing the relevant parameters of the alkali leaching process on the basis of Example 1 resulted in no significant change in the quality of the prepared rutile. Therefore, from the perspective of economy, the comprehensive production effect of Example 1 is relatively better.
[0144] 2. Investigate the effects of different acid leaching processes in S2 on the quality of subsequent rutile preparation:
[0145] By comparing Example 20 and Example 21 with Example 1, lowering the relevant parameters of the acid leaching process on the basis of Example 1 resulted in a decrease in the quality of the prepared rutile, while increasing the relevant parameters of the acid leaching process on the basis of Example 1 resulted in no significant change in the quality of the prepared rutile. Therefore, from the perspective of economy, the comprehensive production effect of Example 1 is relatively better.
[0146] Example 22: This example differs from Example 1 in that the water immersion treatment parameters in step S3, specifically, the liquid-solid ratio of pure water to refined titanium slag is 5:1, the water immersion temperature is 45°C, and the water immersion time is 20 min.
[0147] Example 23: This example differs from Example 1 in that the water immersion treatment parameters in step S3, specifically, the liquid-solid ratio of pure water to refined titanium slag is 10:1, the water immersion temperature is 60°C, and the water immersion time is 30 minutes.
[0148] In order to explore the influence of the S3 production parameter on the quality of the prepared rutile in the method of the present invention, the TiO2 content in the rutile prepared in the above embodiments is measured by the above determination method, and the results are shown in Table 4:
[0149] Table 4 Statistics of TiO2 content in rutile
[0150] Group <![CDATA[TiO2 content / %]]> Embodiment 22 99.22 Embodiment 23 99.50
[0151] It can be seen from Table 4 that, through the comparison between Example 22 and Example 23 and Example 1, lowering the relevant parameters of the water immersion treatment on the basis of Example 1 resulted in a decrease in the quality of the prepared rutile, while increasing the relevant parameters of the water immersion treatment on the basis of Example 1 resulted in no significant change in the quality of the prepared rutile. Therefore, from the perspective of economy, the comprehensive production effect of Example 1 is relatively better.
[0152] Example 24: This example is different from Example 1 in that the rutile preparation parameters in step S4 are as follows: specifically, the slurry in S3 is filtered, the filtered residue is washed with pure water until it becomes neutral, and then dried at 60°C for 1 hour to obtain powdered rutile.
[0153] Example 25: This example is different from Example 1 in that the rutile preparation parameters in step S4, specifically, filtering the slurry in S3, washing the filtered residue with pure water until it is neutral, and then drying at 60°C for 2h to obtain powdered rutile.
[0154] In order to explore the influence of the S4 production parameters on the quality of the prepared rutile in the method of the present invention, the TiO2 content in the rutile prepared in the above embodiments is measured by the above-mentioned determination method, and the results are shown in Table 5:
[0155] Table 5 Statistics of TiO2 content in rutile
[0156] Group <![CDATA[TiO2 content / %]]> Embodiment 24 99.42 Embodiment 25 99.49
[0157] It can be seen from Table 5 that, through the comparison between Example 24 and Example 25 and Example 1, lowering the rutile preparation parameters on the basis of Example 1 results in a certain degree of decrease in the quality of the prepared rutile, while increasing the rutile preparation parameters on the basis of Example 1 results in no significant change in the quality of the prepared rutile. Therefore, from the perspective of economy, the comprehensive production effect of Example 1 is relatively better.
Claims
1. A method for producing rutile based on redox-acid-base leaching, comprising the following steps: S1. Oxidation-reduction treatment: treating low-grade titanium slag by oxidation process and reduction process in sequence to obtain high-titanium slag; S2, acid-base treatment: using alkali leaching process and acid leaching process to treat the high titanium slag treated by S1 in sequence to obtain refined titanium slag; S3, water immersion treatment: the refined titanium slag obtained in S2 is mixed evenly in pure water to obtain a slurry; S4, rutile preparation: filtering, washing and drying the slurry in S3 to obtain rutile; It is characterized in that, in the reduction process of S1, the reducing agent used is a carbon-based reducing agent, and the preparation method of the carbon-based reducing agent is as follows: SA1, preparing spinning solution; Resorcinol and F127 are placed in DMF, stirred for 30 to 40 minutes, and then ultrasonically treated for 1 hour to 1.5 hours to prepare a spinning solution; Let n be the multiplication coefficient and n∈R + , then the amount of resorcinol added is n[10,20]mmol, the amount of F127 added is n[0.5,1]mmol, and the amount of DMF added is n[10,15]g; SA2, preparing fiber silk carrier; The spinning solution prepared in SA1 was used as a raw material to prepare a fiber carrier by an electrospinning process; The parameters of the electrospinning process are: positive electrode voltage of 20-30 kV, drum speed of 120-130 r / min, receiving distance of 15-17 cm, temperature of 25±2°C, humidity of 25±2%, and injection rate of 0.08-0.1 mm / min; SA3, prepare pulling solution; Mix 37 wt.% hydrochloric acid, 10 wt.% boric acid and 37 wt.% formaldehyde solution, and stir ultrasonically for 15 to 20 minutes to obtain a pulling solution; Let n be the multiplication coefficient and n∈R + , then the amount of 37wt.% hydrochloric acid added is n[5,8]mL, the amount of 10wt.% boric acid added is n[20,25]mL, and the amount of 37wt.% formaldehyde solution added is n[30,40]mL; SA4, fiber processing; The fiber carrier prepared in SA2 is fixed on an impregnation and pulling machine, immersed in the pulling liquid prepared in SA3, and the fiber is obtained by pulling. The pulling speed is set to 2-3 mm / s, and the immersion time is 4-6 h. SA5. Preparation of carbon-based reducing agent; First, the fiber filaments in SA4 are dried at 100°C for 24 hours, then washed with pure water and dried at 60°C for 20-30 minutes, and finally heated at a gradient temperature. After the reaction is complete, the fiber filaments are cooled to room temperature in the furnace to obtain a carbon-based reducing agent. The gradient temperature in the SA5 is: rising from room temperature to 100°C at a rate of 1-2°C / min, and keeping warm for 10-15min; then rising to 600°C at a rate of 3-5°C / min, and keeping warm for 2-3h.
2. A method for producing rutile based on redox-acid-base leaching as claimed in claim 1, characterized in that: The oxidation process in S1 is: S1-1, firstly, the low-grade titanium slag is ground to 100-150 μm by ball milling process, and then dried at 100°C for 3-4 hours; The parameters of ball milling process are: the speed of material tank is 60-70rpm, the speed of chassis is 200-220rpm, the ball milling time is 20-25min, and the ball-to-material ratio is 4:1; S1-2, sintering the low-grade titanium slag treated in S1-1 at a gradient temperature, and finally cooling it to room temperature with the furnace to obtain titanium oxide slag, i.e., high-titanium slag; The gradient temperature in S1-2 is: rising from room temperature to 100°C at a rate of 10-15°C / min, and keeping warm for 5-10 minutes; then rising to 500°C at a rate of 10-15°C / min, and keeping warm for 30-40 minutes; finally rising to 1100°C at a rate of 15-20°C / min, and keeping warm for 1-1.5 hours.
3. A method for producing rutile based on redox-acid-base leaching as claimed in claim 2, characterized in that: The reduction process in S1 is: S1-3, uniformly mixing the titanium oxide slag in S1-2 with the carbon-based reducing agent, and cold isostatically pressing at 60-100 MPa in a mold to form a titanium slag blank; Let n be the multiplication coefficient and n∈R + , then the amount of titanium oxide slag added in S1-3 is n[20,25]g, and the amount of carbon-based reducing agent added is n[2,3]g; S1-4, placing the titanium slag blank in a tubular furnace for heating, firstly introducing an inert gas at a rate of 2 to 2.5 L / min, and exhausting the gas for 10 to 15 minutes; then performing a reduction reaction at a gradient temperature, and cooling the furnace to room temperature to obtain reduced titanium slag; The gradient temperature in S1-4 is: rising from room temperature to 100°C at a rate of 10-15°C / min, and keeping warm for 5-10 minutes; then rising to 700°C at a rate of 10-15°C / min, and keeping warm for 20-30 minutes; then rising to 850°C at a rate of 15-20°C / min, and keeping warm for 20-30 minutes; then rising to 900°C at a rate of 20-25°C / min, and keeping warm for 1-1.5 hours.
4. A method for producing rutile based on redox-acid-base leaching as claimed in claim 1, characterized in that: The alkali leaching process in S2 is: S2-1, placing the high titanium slag treated by S1 into a high pressure reactor, adding 30wt.% NaOH solution and mixing evenly, and then performing alkali leaching to obtain alkali leached titanium slag; The liquid-solid ratio of 20wt.% NaOH solution to high-titanium slag is 3-4:1, the oxygen partial pressure is 1-1.5MPa, the alkali leaching temperature is 180-210°C, and the leaching time is 1.5-2h.
5. A method for producing rutile based on redox-acid-base leaching as claimed in claim 4, characterized in that: The acid leaching process in S2 is: S2-2, placing the alkali-leached titanium slag in S2-1 into a high-pressure reactor, adding 30wt.% H2SO4 solution and mixing evenly, and then performing acid leaching to obtain acid-leached titanium slag, i.e., refined titanium slag; Among them, the liquid-to-solid ratio of 20wt.% H2SO4 solution to alkaline leached titanium slag is 8-10:1, the oxygen partial pressure is 2.5-3MPa, the acid leaching temperature is 80-120°C, and the leaching time is 2-3h.
6. A method for producing rutile based on redox-acid-base leaching as claimed in claim 1, characterized in that: The water immersion process in S3 is as follows: the refined titanium slag obtained in S2 is mixed evenly with pure water to obtain a slurry. The refined titanium slag treated with S2 is placed in a reactor, pure water is added and mixed evenly, and water-immersed to obtain slurry; Among them, the liquid-solid ratio of pure water to refined titanium slag is 5-10:1, the water immersion temperature is 45-60°C, and the water immersion time is 20-30 minutes.
7. A method for producing rutile based on redox-acid-base leaching as claimed in claim 1, characterized in that: The preparation process of rutile in S4 is as follows: filtering the slurry in S3, washing the filtered residue with pure water until it becomes neutral, and then drying it at 60° C. for 1 to 2 hours to obtain powdered rutile.